The importance of diabatic processes for the dynamics of synoptic-scale extratropical weather systems – a review - H. Wernli; S. L. Gray (Weather and Climate Dynamics)
Many fundamental concepts of synoptic-scale extratropical dynamics are based on the quasi-geostrophic equations of a dry atmosphere. This “dry dynamics” provides the essential understanding of, for example, the formation of extratropical cyclones and the propagation of Rossby waves and makes potential vorticity (PV) a materially conserved quantity. Classically, for extratropical weather systems, the importance of so-called “diabatic effects”, e.g. surface fluxes, phase changes of water in clouds, and radiation, has been regarded as secondary compared to the dry dynamical processes. As outlined in this review article, research during recent decades has modified this view of the role of diabatic processes. A combination of complementary research approaches revealed that the nonlinear dynamics of extratropical cyclones and upper-tropospheric Rossby waves is affected – in some cases strongly – by diabatic processes. Despite the violation of material PV conservation in the presence of diabatic processes, the concept of PV has been of utmost importance to identify and quantify the role of diabatic processes and to integrate their effects into the classical understanding based on dry dynamics. This review first summarises the theoretical concepts of diabatic PV modification, moist PV, and slantwise moist convection and provides a concise overview of early research on diabatic effects until the late 1970s. Two poorly predicted high-impact cyclones affecting eastern North America then triggered an impressive diversity of efforts to investigate the role of diabatic processes in rapid cyclone intensification in the last 2 decades of the 20th century. These research activities, including the development of sophisticated diagnostics, growing applications of the Lagrangian perspective, real-case and idealised numerical experiments, and dedicated field experiments, are reviewed in detail. This historical perspective provides insight about how societal relevance, international collaboration, technical development, and creative science contributed to establishing this important theme of dynamical meteorology. The second part of the review then more selectively outlines important achievements in the last 2 decades in our understanding of how diabatic effects, in particular those related to cloud microphysics, affect the structure, dynamics, and predictability of different types of extratropical cyclones and their mesoscale substructures, upper-tropospheric blocks, Rossby waves, and interactions. A novel aspect is the relevance of research on diabatic processes for climate change research. The review closes by highlighting important implications of investigating diabatic processes in extratropical weather systems for the broader field of weather and climate dynamics and its fundamentals and representation in numerical models.